Endothelial cells regulate astrocyte to neural progenitor cell trans-differentiation in a mouse model of stroke - Li, Wenlu; Mandeville, Emiri T.; Durán-Laforet, Violeta; Fukuda, Norito; Yu, Zhanyang; Zheng, Yi; Held, Aaron; Park, Ji-Hyun; Nakano, Takafumi; Tanaka, Masayoshi; Shi, Jingfei; Esposito, Elga; et al. (Nature communications, 2022)
The concept of the neurovascular unit emphasizes the importance of cell-cell signaling between neural, glial, and vascular compartments. In neurogenesis, for example, brain endothelial cells play a key role by supplying trophic support to neural progenitors. Here, we describe a surprising phenomenon where brain endothelial cells may release trans-differentiation signals that convert astrocytes into neural progenitor cells in male mice after stroke. After oxygen-glucose deprivation, brain endothelial cells release microvesicles containing pro-neural factor Ascl1 that enter into astrocytes to induce their trans-differentiation into neural progenitors. In mouse models of focal cerebral ischemia, Ascl1 is upregulated in endothelium prior to astrocytic conversion into neural progenitor cells. Injecting brain endothelial-derived microvesicles amplifies the process of astrocyte trans-differentiation. Endothelial-specific overexpression of Ascl1 increases the local conversion of astrocytes into neural progenitors and improves behavioral recovery. Our findings describe an unexpected vascular-regulated mechanism of neuroplasticity that may open up therapeutic opportunities for improving outcomes after stroke. Damaged brains try to repair themselves by producing neurons in areas where neurogenesis does not normally occur. Here, the authors show that brain endothelial cells provide microvesicle-encased signals that convert parenchymal astrocytes into neural progenitors, thus improving outcomes after stroke.